Characterization of a Pyrethroid-Degrading Pseudomonas fulva Strain P31 and Biochemical Degradation Pathway of D-Phenothrin - Yang, Jingjing; Feng, Yanmei; Zhan, Hui; Liu, Jie; Yang, Fang; Zhang, Kaiyang; Zhang, Lianhui; Chen, Shaohua (Frontiers in Microbiology, 2018)
D-phenothrin is one of the most popular pyrethroid insecticides for its broad spectrum and high insecticidal activity. However, continuous use of D-phenothrin has resulted in serious environmental contamination and raised public concern about its impact on human health. Biodegradation of D-phenothrin has never been investigated and its metabolic behaviors remain unknown. Here, a novel bacterial strain P31 was isolated from active sludge, which completely degraded (100%) D-phenothrin at 50 mg·L-1 in 72 h. Based on the morphology, 16S rRNA gene and Biolog tests, the strain was identified as Pseudomonas fulva. Biodegradation conditions were optimized as 29.5 °C and pH 7.3 by utilizing response surface methodology (RSM). Strain P31 depicted high tolerance and strong D-phenothrin degradation ability through hydrolysis pathway. Strain P31 degraded D-phenothrin at inhibition constant (Ki) of 482.1673 mg·L−1 and maximum specific degradation constant (qmax) of 0.0455 h-1 whereas critical inhibitor concentration remained as 41.1189 mg·L-1. 3-Phenoxybenzaldehyde and 1,2-benzenedicarboxylic butyl dacyl ester were identified as the major intermediate metabolites of D-phenothrin degradation pathway through high-performance liquid chromatography (HPLC) and gas chromatography-mass spectrometry (GC-MS). Bioaugmentation of D-phenothrin-contaminated soils with strain P31 dramatically enhanced its degradation, and over 75% of D-phenothrin was removed from soils within 10 days. Moreover, the strain illustrated a remarkable capacity to degrade other synthetic pyrethroids, including permethrin, cyhalothrin, β-cypermethrin, deltamethrin, fenpropathrin, and bifenthrin, exhibiting great potential in bioremediation of pyrethroid-contaminated environment.